RANCANG BANGUN ALAT PEMOTONG/PENGIRIS BAHAN BAKU KRUPUK TERIGU DAN KRIPIK SINGKONG - Widiyarta, I.M.; Negara, D.N.K.P.; Muku, I.D.M.K. (Buletin Udayana Mengabdi, 2018)
Micro business of wheat flour chips and cassava chips is a home business that many families do in Buleleng and Karangasem regency. In that home-based business, they are generally facing the similar problems such as relatively low of efficiency and productivity. These problems are caused in the process of cutting or slicing raw material of chips that is still processed conventionally so it takes a long time. In this article, the slicing machine of chips is designed with cutting speed reaches of about 120 pieces/minute. The machine has three main parts such as the driving part of 0.25Hp DC-Motor, the slicing section with disk knife and guide section of sliced chips.